Virtual Reality Treatment Displaying the Missing Leg Improves Phantom Limb Pain: A Small Clinical Trial. (December 2021) - Ambron, Elisabetta; Buxbaum, Laurel J.; Miller, Alexander; Stoll, Harrison; Kuchenbecker, Katherine J.; Coslett, H. Branch
Background: Phantom limb pain (PLP) is a common and in some cases debilitating consequence of upper- or lower-limb amputation for which current treatments are inadequate. Objective: This small clinical trial tested whether game-like interactions with immersive VR activities can reduce PLP in subjects with transtibial lower-limb amputation. Methods: Seven participants attended 5–7 sessions in which they engaged in a visually immersive virtual reality experience that did not require leg movements (Cool! TM ), followed by 10–12 sessions of targeted lower-limb VR treatment consisting of custom games requiring leg movement. In the latter condition, they controlled an avatar with 2 intact legs viewed in a head-mounted display (HTC Vive TM ). A motion-tracking system mounted on the intact and residual limbs controlled the movements of both virtual extremities independently. Results: All participants except one experienced a reduction of pain immediately after VR sessions, and their pre session pain levels also decreased over the course of the study. At a group level, PLP decreased by 28% after the treatment that did not include leg movements and 39.6% after the games requiring leg motions. Both treatments were successful in reducing PLP. Conclusions: This VR intervention appears to be an efficacious treatment for PLP in subjects with lower-limb amputation.